The influence of organofluorine compounds on cultivation of Enterobacteriaceae - Пришляк, Р. І.; Голубіцька, В. О. (Problems of Environmental Biotechnology, 2016)
Investigated the influence of organofluorine compounds, as one of the main growth factors for Enterobacteriaceae. Compared the basic methods of fluordecaline sterilization. The results make it possible to choose the optimal concentration fluordecaline and analyze the growth curve of E. coli.